2006
DOI: 10.1007/s00701-006-0816-3
|View full text |Cite
|
Sign up to set email alerts
|

The midline suboccipital subtonsillar approach to the hypoglossal canal: surgical anatomy and clinical application

Abstract: Primary lesions of the hypoglossal canal, such as hypoglossal schwannomas, are rare. No consensus exists with regard to the surgical approach of choice for treatment of these lesions. Usually, lateral transcondylar approaches have been used. The authors describe the surgical anatomy of the midline subtonsillar approach to the hypoglossal canal. This approach includes a midline suboccipital craniotomy, dorsal opening of the foramen magnum and elevation of ipsilateral cerebellar tonsil to expose the hypoglossal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Table II and Figures 1 to 7, with no significant differences in regard to sex. The laterality was significantly different between the right and left sides only in the measurement shown in between the HC and the OC is crucial in the TA (Bozbuga et al, 1998), and the OC maximum pierceable amount without opening the posterior edge of the HC is 1 / 3 or 1⁄2 posterior of the long axis of the OC (Rhoton;Marin Sanabria et al 2002;Tatagiba et al, 2006). The values of 10.3 mm on the right side, and of 11.3 mm on the left side for the mean distance between the HC and the posterior edge of the OC, found in this study (Table I, (Table I, A4) are also in accordance to the values reported by Muthukumar et al and Barut et al The structure of the septum of the HC must also be examined, because if two or three parts of the canal are not identified prior to surgery, the nerve of the HC can be injured (Katsuta et al, Table I.…”
Section: Resultsmentioning
confidence: 95%
“…Table II and Figures 1 to 7, with no significant differences in regard to sex. The laterality was significantly different between the right and left sides only in the measurement shown in between the HC and the OC is crucial in the TA (Bozbuga et al, 1998), and the OC maximum pierceable amount without opening the posterior edge of the HC is 1 / 3 or 1⁄2 posterior of the long axis of the OC (Rhoton;Marin Sanabria et al 2002;Tatagiba et al, 2006). The values of 10.3 mm on the right side, and of 11.3 mm on the left side for the mean distance between the HC and the posterior edge of the OC, found in this study (Table I, (Table I, A4) are also in accordance to the values reported by Muthukumar et al and Barut et al The structure of the septum of the HC must also be examined, because if two or three parts of the canal are not identified prior to surgery, the nerve of the HC can be injured (Katsuta et al, Table I.…”
Section: Resultsmentioning
confidence: 95%
“…The approaches have been lateral transcondylar, suboccipital or midline suboccipital subtonsillar. [147] Ichimura et al . preserved the FM and condyle in one out of seven patients; this patient had largely extradural tumor eroding the jugular foramen.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Midline subtonsillar approach provides adequate approach in most of the cases allowing tumor removal with the brainstem, posterior inferior cerebellar artery and lower cranial nerves under direct vision. [4] The goal of tumor removal can be achieved by keeping it simple, and avoiding the morbidity associated with the extensive transcondylar approaches. postoperative day.…”
Section: Introductionmentioning
confidence: 99%
“…The STA gives excellent access, providing a panoramic view of the foramen of Luschka laterally and up to the middle cerebellar peduncle [ 4 ]. However, the STA has not yet been described for resecting meningiomas of the hypoglossal canal although the suboccipital midline approach allows tumor removal through a direct angle of view.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of treatment approach depends on several factors, including tumor type, size, compression of neural structures, patient age, symptoms and co-morbid conditions. Should surgery be considered, there is currently no consensus regarding the ideal surgical approach for treating these lesions [ 4 ]. Commonly used approaches for accessing the hypoglossal canal are the lateral transcondylar and far-lateral supracondylar approaches [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%